2009
DOI: 10.1186/1476-069x-8-37
|View full text |Cite
|
Sign up to set email alerts
|

Urogenital abnormalities in men exposed to diethylstilbestrol in utero: a cohort study

Abstract: BackgroundDiethylstilbestrol (DES), a synthetic estrogen widely prescribed to pregnant women during the 1940s-70s, has been shown to cause reproductive problems in the daughters. Studies of prenatally-exposed males have yielded conflicting results.MethodsIn data from a collaborative follow-up of three U.S. cohorts of DES-exposed sons, we examined the relation of prenatal DES exposure to occurrence of male urogenital abnormalities. Exposure status was determined through review of prenatal records. Mailed questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
74
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(80 citation statements)
references
References 24 publications
(28 reference statements)
3
74
0
Order By: Relevance
“…This was supported by clinical studies showing that the xenoestrogen diethylstilbestrol (DES) given to pregnant mothers in the 1940s-1970s led to a high incidence of cryptorchidism in the male children (Palmer et al 2009), as well as the key experimental study showing that DES given to pregnant mice caused bilateral cryptorchidism and a downregulation of Insl3 gene expression in the fetal testis (Emmen et al 2000b). Later studies on rats then showed that the cryptorchidism and other TDS-like effects induced in rats by administering phthalates during a critical window of testis differentiation also led to a marked downregulation of fetal Insl3 expression (McKinnell et al 2005, Mahood et al 2006.…”
Section: Fetal Insl3 and Endocrine Disruptionmentioning
confidence: 96%
“…This was supported by clinical studies showing that the xenoestrogen diethylstilbestrol (DES) given to pregnant mothers in the 1940s-1970s led to a high incidence of cryptorchidism in the male children (Palmer et al 2009), as well as the key experimental study showing that DES given to pregnant mice caused bilateral cryptorchidism and a downregulation of Insl3 gene expression in the fetal testis (Emmen et al 2000b). Later studies on rats then showed that the cryptorchidism and other TDS-like effects induced in rats by administering phthalates during a critical window of testis differentiation also led to a marked downregulation of fetal Insl3 expression (McKinnell et al 2005, Mahood et al 2006.…”
Section: Fetal Insl3 and Endocrine Disruptionmentioning
confidence: 96%
“…For example, prenatal exposure to estrogen can feminize male external genitalia in humans (16,48,49) but has little effect in mice. Such differences likely reflect differences in gestational time because humans have a relatively long period of prenatal development compared with mice and, therefore, the neonatal phase of genital development in mice is comparable with prenatal development in humans (47,50).…”
Section: Discussionmentioning
confidence: 99%
“…6 Mothers administered DES during pregnancy have an increased risk of breast cancer incidence 7 and mortality. 8 Sons who were exposed in utero have an increased risk of genitourinary defects 9 and a possible increase in testicular cancer. 10 The possibility of epigenetic transmission with consequent adverse outcomes in the offspring of prenatally exposed women is under investigation.…”
mentioning
confidence: 99%